DEFI-ACCESS - Aplicativo Com Informações E Serviços De Equipes Multidisciplinares Para Pessoas Com Deficiência E Seus Familiares - Ribas, Cassio Roberto Urbani [UNIFESP] (2018)
Introduction: There are more smartphones in Brazil than number of inhabitants. Access to information is important, since any information can be obtained instantly, with immediate circulation, of news and services.. It is difficult to access much of the information presented on the INTERNET through analyzes, opinions are often mismatched and without any guarantee of provenance and truthfulness. Rather than grounding knowledge and assisting decision making, they eventually cause a dispersal of informational content, which can lead to conclusions and wrong decisions. Given the lack of APP for "smartphones" aimed at providing services, there is a need to create an APP, in which content, according to the professional area, inserted in the APP, which in an intuitive can access information and obtain guidance on a particular topic, problem or answers to doubts. Objective: To develop an application with information and services of multidisciplinary teams for people with disabilities and their families. Methods: An antecedent search of APP was performed in the databases: (Google and Google Scholar). For the development of APP, the Design Thinking methodology was used, which is divided in four phases: Discover / Empathy, Define, Develop / Prototype and Deliver. Test. The prototype of the APP, called DEFI-ACCESS, were produced. Results: The final APP presents all the defined functionality that was used by the Design Thinking method. Conclusion: The application was designed in WEB APP format, called DEFI-ACCESS - application for people with disabilities and their families.